2009
DOI: 10.1167/iovs.08-2083
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Phenotype–Genotype Correlations in Spanish Patients withRDH12Mutations

Abstract: The RDH12-associated phenotype is not homogeneous, the position and nature of the mutations clearly influence the pathologic expression of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…Another study closely followed and reported 11 distinct RDH12 mutations in homozygosity or compound heterozygosity in 8/44 patients with LCA who were affected with the congenital severe yet progressive rod-cone dystrophy form of the disease [16]. To date, over 60 different RDH12 mutations have been reported predominantly in LCA patients [1517, 21, 2327] but also in early-onset retinal dystrophy [8, 15, 20, 21, 24, 25], in families with arRP [26, 27], and in a family with autosomal dominant RP [19]. These findings above have shown that mutations in the human RDH12 gene are responsible for severe forms of blindness.…”
Section: Discussionmentioning
confidence: 99%
“…Another study closely followed and reported 11 distinct RDH12 mutations in homozygosity or compound heterozygosity in 8/44 patients with LCA who were affected with the congenital severe yet progressive rod-cone dystrophy form of the disease [16]. To date, over 60 different RDH12 mutations have been reported predominantly in LCA patients [1517, 21, 2327] but also in early-onset retinal dystrophy [8, 15, 20, 21, 24, 25], in families with arRP [26, 27], and in a family with autosomal dominant RP [19]. These findings above have shown that mutations in the human RDH12 gene are responsible for severe forms of blindness.…”
Section: Discussionmentioning
confidence: 99%
“…While human RDH12 and other mammalian RDH12-related retinaldehyde reductases have been a focus of numerous studies [12-14, 32, 36-38], no analysis has been performed to trace the origins of this gene family. To address this question, we expanded our search of RDH12 homologs to non-vertebrate species, for which whole genome sequencing data became available.…”
Section: Resultsmentioning
confidence: 99%
“…This mutation was not reported in a recent investigation of RDH12 mutations associated with severe and early onset retinal dystrophies in Spanish patients. 8 Both mutations can potentially cause significant alterations in protein structure and activity; it is still unclear whether the loss of RDH12 function may lead to retinal dystrophy by reducing visual pigment regeneration or by determining production and storage of toxic intermediates.…”
Section: Discussionmentioning
confidence: 99%